(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Dutasteride and Silodosin both are approved drugs by USFDA (Food & Drug Administration). On literature survey, it was found that few method have been reported for simultaneous estimation of Dutasteride and Silodosin. Therefore, it was thought of interest to develop a simple, accurate, precise, sensitive and economic analytical method and to validate as per ICH guidelines. So RP-HPLC method was developed and validated for simultaneous estimation of Dutasteride and Silodosin in multiunit system. Separation was achieved on Shimadzu HPLC; Agilent C18 Column (250×4.6mm,5µm ) by using a mobile phase containing Methanol : Water in 50:50 v/v ratio. Analysis was done at the filow rate of 1.0 ml/mint and PDA detection was carried out by wavelength at 280 nm. The retention time of Silodosin and Dutasteride was found to be 2.050 min & 2.623 min respectively. The method was validated in terms of linearity, precision, accuracy, specificity, robustness etc. The linearity was found to be in the range of 10-50 µg/ml for both Silodosin and Dutasteride with correlation coefficient of 0.999 for Silodosin and 0.999 for Dutasteride. %RSD of method precision was found to be less than 2%. This indicates that the method is precise.